Anode materials and fluoride ion batteries

By using a combination of Mg element and fluoride ion conductive material in the negative electrode material of the fluoride ion battery, the problem of the battery's operating voltage drop during short circuit is solved, and more stable battery performance is achieved.

CN114927652BActive Publication Date: 2025-02-14TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210099549.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-12
Filing Date
2022-01-27
Publication Date
2025-02-14
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

The existing fluoride ion battery suppresses the occurrence of short circuits, and causes the operating voltage to drop.

Method used

By using an Mg material containing Mg elements and a negative electrode material containing at least one metal element and F element, the Mg material is used with the fluoride ion conductive material to suppress the occurrence of a short circuit and prevent the operating voltage from dropping.

Benefits of technology

It effectively suppresses the occurrence of short circuits, prevents the decrease in the working voltage, and improves the working performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114927652B_ABST
    Figure CN114927652B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode material and a fluoride ion battery. The main purpose is to provide a negative electrode material, which is a negative electrode material for a fluoride ion battery, which can suppress the occurrence of short circuits and suppress the decrease in working potential. In the present disclosure, the above-mentioned problems are solved by providing the following negative electrode material, which is a negative electrode material for a fluoride ion battery, comprising: a Mg material containing Mg element, and a fluoride ion conductive material containing at least one metal element (excluding Mg element) and F element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to negative electrode materials. Background Art

[0002] As a high voltage and high energy density battery, for example, a Li ion battery is known. A Li ion battery is a cation-based battery using Li ions as charge carriers. On the other hand, as an anion-based battery, a fluoride ion battery using fluoride ions (fluoride ions) as charge carriers is known.

[0003] For example, Patent Document 1 discloses a fluoride ion battery in which a power generation element of the battery can be formed of two components, namely a specific electrode layer and a solid electrolyte layer. In addition, in the battery of Patent Document 1, it is disclosed that a metal material having a metal element such as Pb, Sn, In, Bi, Sb is used in the solid electrolyte layer or the negative electrode current collector.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-077987 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In Patent Document 1, a negative electrode active material is self-formed from a solid electrolyte by utilizing a defluorination reaction of a solid electrolyte. Furthermore, by using a specific metal material in a solid electrolyte layer or a negative electrode current collector, the occurrence of a short circuit is suppressed. As in Patent Document 1, by using a specific metal material for the self-formed negative electrode active material, the occurrence of a short circuit can be suppressed, but since the reaction potential of the negative electrode active material migrates to the high potential side, a new problem of a decrease in the operating potential of the battery is generated.

[0009] The present disclosure is made in view of the above-mentioned actual situation, and its main purpose is to provide a negative electrode material for a fluoride ion battery, which is a negative electrode material that can suppress the decrease in operating voltage while suppressing the occurrence of short circuit.

[0010] Means for solving problems

[0011] In order to solve the above problems, the present disclosure provides a negative electrode material for a fluoride ion battery, comprising: a Mg material containing the Mg element, and a fluoride ion conductive material containing at least one metal element and the F element, wherein the metal element does not include the Mg element.

[0012] According to the present disclosure, by using a Mg material together with a fluoride ion conductive material, a negative electrode material can be obtained that can suppress a decrease in operating voltage while suppressing the occurrence of a short circuit.

[0013] In the above disclosure, the Mg material may be a single substance of Mg.

[0014] In the above disclosure, the fluoride ion conductive material can function as a negative electrode active material during charge and discharge.

[0015] In the above disclosure, the fluoride ion conductive material may contain two or more of the above metal elements.

[0016] In the above disclosure, the fluoride ion conductive material may contain Ca element, Ba element and F element.

[0017] In the above disclosure, the fluoride ion conductive material may be Ca 1-x Ba x F2 (x satisfies 0.45≦x≦0.65).

[0018] In the above disclosure, the above fluoride ion conductive material may contain La element, Ba element and F element.

[0019] The present disclosure also provides a fluoride ion battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer contains the negative electrode material described above.

[0020] According to the present disclosure, the negative electrode layer contains the negative electrode material, thereby achieving a fluoride ion battery that can suppress a decrease in operating voltage while suppressing the occurrence of a short circuit.

[0021] In the above disclosure, the solid electrolyte in the above solid electrolyte layer may contain the above metal element and F element.

[0022] In the above disclosure, the ion conductivity of the solid electrolyte in the solid electrolyte layer may be equal to or higher than the ion conductivity of the fluoride ion conductive material in the negative electrode layer.

[0023] Effects of the Invention

[0024] The present disclosure achieves the effect of being able to provide a negative electrode material for a fluoride ion battery that can suppress a decrease in operating voltage while suppressing the occurrence of a short circuit. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic cross-sectional view showing an example of a fluoride ion battery in the present disclosure.

[0026] Figure 2 These are the results of XRD measurement of the negative electrode materials obtained in Examples 1 to 5.

[0027] Figure 3 The charge and discharge curves of Examples 1 to 5 and Comparative Example 1 are shown.

[0028] Figure 4 It is a graph comparing the capacities of Examples 1 to 5.

[0029] Figure 5 The charge and discharge curves of Example 6 and Comparative Example 2 are shown in FIG.

[0030] Description of Reference Numerals

[0031] 1… Positive electrode layer

[0032] 2…Solid electrolyte layer

[0033] 3…Negative electrode layer

[0034] 4…Positive electrode collector

[0035] 5…Negative electrode collector

[0036] 6…Battery housing

[0037] 10…Fluoride ion battery DETAILED DESCRIPTION

[0038] The negative electrode material and the fluoride ion battery in the present disclosure are described in detail below.

[0039] A. Negative electrode materials

[0040] The negative electrode material in the present disclosure is a negative electrode material for a fluoride ion battery, and contains: a Mg material containing the Mg element, and a fluoride ion conductive material containing at least one metal element (excluding the Mg element) and the F element.

[0041] According to the present disclosure, by using Mg material together with fluoride ion conductive material, it becomes a negative electrode material that can suppress the decrease in operating voltage while suppressing the occurrence of short circuit. As mentioned above, in Patent Document 1, the defluorination reaction of the solid electrolyte is utilized to self-form the negative electrode active material from the solid electrolyte. Furthermore, by using a specific metal material in the solid electrolyte layer or the negative electrode collector, the occurrence of short circuit is suppressed. As in Patent Document 1, although the occurrence of short circuit can be suppressed by using a specific metal material for the self-formed negative electrode active material, the reaction potential of the negative electrode active material migrates to the high potential side, thus generating a new problem of lowering the operating potential of the battery.

[0042] Specifically, the reaction potential (defluorination potential, fluorination reaction potential) of the fluoride ion conductive material functioning as a negative electrode active material source shifts to the high potential side (+ potential side) by 0.5 to 0.7 vs. Pb due to the action of the added metal material (Pb, Sn, In, B, or Sb). 2+As a result, the potential difference between the positive electrode active material and the negative electrode active material becomes smaller, and the operating voltage of the battery decreases. In contrast, in the present disclosure, by using Mg material as the metal material, the migration amount can be kept at 0.3vs.Pb 2+ As a result, by using the Mg material, it is possible to suppress the occurrence of short circuits while suppressing a decrease in the operating voltage.

[0043] Furthermore, the mechanism by which the reaction potential of the fluoride ion conductive material changes due to the addition of the metal material is not yet clear. It is believed that the reason is that at the beginning of discharge or during discharge, chemical bonding occurs rapidly electrochemically between the metal material and the solid electrolyte, causing the electronic structure (band structure) of the solid electrolyte to change, and the Fermi level of the material, a parameter directly related to the electrode potential, changes.

[0044] In addition, the mechanism that can suppress the occurrence of short circuits is described using a fluoride ion battery having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer in sequence. The defluorination / fluorination reaction potential of the fluoride ion conductive material in the negative electrode layer slightly migrates to the high (+) potential side under the coexistence of the Mg material. Thus, during discharge (the potential of the battery changes to the low (-) side), defluorination of the fluoride ion conductive material in the negative electrode layer occurs before defluorination of the solid electrolyte in the solid electrolyte layer. Therefore, the generation of discharge products (metals from the solid electrolyte) in the solid electrolyte layer can be prevented. As a result, the occurrence of short circuits can be suppressed.

[0045] The negative electrode material disclosed in the present invention contains: a Mg material containing the Mg element. The Mg material may be a single substance Mg or a Mg alloy. The Mg alloy is preferably an alloy with Mg as the main component. The proportion of the Mg element in the Mg alloy is, for example, 50 atomic % or more, 70 atomic % or more, or 90 atomic % or more. The proportion of the Mg element in the Mg alloy can be determined, for example, by ICP emission spectrometry. The negative electrode material may contain only one Mg material or two or more Mg materials. In addition, the negative electrode material preferably contains at least a single substance Mg.

[0046] The shape of the Mg material may be, for example, a particle shape. 50 ) is, for example, 0.1 μm or more and 50 μm or less. The average particle size (D 50 ) can be obtained from the results of particle size distribution measurement obtained using a laser diffraction scattering method.

[0047] The ratio of the Mg material in the negative electrode material is, for example, 20 wt % or more, 30 wt % or more, or 40 wt % or more. On the other hand, the ratio of the Mg material is, for example, 50 wt % or less.

[0048] In addition, the negative electrode material in the present disclosure contains: a fluoride ion conductive material containing at least one metal element (excluding Mg element) and F element. The fluoride ion conductive material has fluoride ion conductivity. In addition, the fluoride ion conductive material functions as a negative electrode active material during charge and discharge. For example, when the fluoride ion conductive material is La 0.9 Ba 0.1 F 2.9 In the case of charging (F - When separated), the following reaction occurs.

[0049] La 0.9 Ba 0.1 F 2.9 +2.7e - →0.9La+0.1BaF2+2.7F -

[0050] That is, the negative electrode active material is self-generated from the fluoride ion conductive material. The negative electrode material in the present disclosure preferably contains a fluoride ion conductive material as the main negative electrode active material. "Main negative electrode active material" means that the capacity from the fluoride ion conductive material (and its charging product) is the largest in the total capacity. In addition, the negative electrode material in the present disclosure may not contain a negative electrode active material other than the fluoride ion conductive material.

[0051] Fluoride ion conductive materials usually contain metal elements M and F elements other than Mg, and have fluoride ion conductivity. As the metal element M, for example, lanthanide elements such as La and Ce, alkaline earth elements such as Ca, Sr, and Ba (excluding Mg), Group 14 elements such as Pb and Sn, and alkali elements such as Li, Na, K, Rb, and Cs can be listed. Among them, the metal element M is preferably at least one of the La element, the Ba element, the Pb element, the Sn element, the Ca element, and the Ce element. This is because a fluoride ion conductive material with good ion conductivity can be obtained. The fluoride ion conductive material may contain only one metal element M, or may contain two or more. In addition, the fluoride ion conductive material may contain at least the Ba element as the metal element M.

[0052] The fluoride ion conductive material preferably contains Ca and Ba as the metal element M. That is, the fluoride ion conductive material preferably contains Ca element, Ba element and F element. This is because a fluoride ion conductive material with good ion conductivity can be obtained. In this case, the fluoride ion conductive material is preferably Ca 1-x Ba xF2 (x satisfies 0<x<1). x may be greater than or equal to 0.45, or greater than or equal to 0.50, or greater than or equal to 0.55. On the other hand, x may be less than or equal to 0.65, or less than or equal to 0.60. In particular, when x satisfies 0.45≦x≦0.65, the reversible capacity becomes good.

[0053] In addition, the fluoride ion conductive material preferably contains La and Ba as the metal element M. That is, the fluoride ion conductive material preferably contains La element, Ba element and F element. This is because a fluoride ion conductive material with good ion conductivity can be obtained. In this case, the fluoride ion conductive material is preferably La. 1-x Ba x F 3-x (x satisfies 0<x<1). x may be 0.05 or more, and may be 0.1 or more. On the other hand, x may be 0.8 or less, and may be 0.6 or less.

[0054] The shape of the fluoride ion conductive material may be, for example, a particle shape. The average particle size (D 50 ) is, for example, greater than or equal to 0.1 μm and less than or equal to 50 μm.

[0055] The proportion of the fluoride ion conductive material in the negative electrode material is, for example, 50 wt % or more, 60 wt % or more, or 70 wt % or more. On the other hand, the proportion of the fluoride ion conductive material is, for example, 90 wt % or less, or 80 wt % or less.

[0056] In addition, the negative electrode material in the present disclosure may further contain at least one of a conductive material (electronic conductive material) and a binder as needed. As a conductive material, for example, a carbon material can be listed. As a carbon material, for example, carbon black such as acetylene black, Ketjen black, furnace black, pyrolytic carbon black, graphene, fullerene, and carbon nanotubes can be listed. On the other hand, as a binder, for example, a fluorine-based binder such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) can be listed.

[0057] In addition, the negative electrode material in the present disclosure may be a composite material of a Mg material and a fluoride ion conductive material. The composite material can be obtained, for example, by mechanically grinding a mixture containing a Mg material and a fluoride ion conductive material.

[0058] The negative electrode material in the present disclosure is generally used in a fluoride ion battery. The fluoride ion battery will be described later.

[0059] B. Fluoride ion battery

[0060] Figure 1 This is a schematic cross-sectional view showing an example of a fluoride ion battery in the present disclosure. Figure 1 The fluoride ion battery 10 shown in the figure has: a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, a negative electrode collector 5 for collecting current from the negative electrode layer 2, and a battery case 6 for accommodating these components. In the present disclosure, the negative electrode layer 2 contains the above-mentioned negative electrode material. In addition, the fluoride ion battery in the present disclosure has a solid electrolyte layer, so it can also be called an all-solid fluoride ion battery.

[0061] According to the present disclosure, the negative electrode layer contains the above-mentioned negative electrode material, thereby achieving a fluoride ion battery that can suppress the occurrence of short circuits and suppress the decrease in operating potential.

[0062] 1. Negative electrode layer

[0063] The negative electrode layer in the present disclosure is a layer containing at least the above-mentioned negative electrode material. The negative electrode material is the same as that described in "A. Negative electrode material", so the description here is omitted. There is no particular limitation on the thickness of the negative electrode layer, and it can be appropriately adjusted according to the structure of the battery.

[0064] 2. Positive electrode layer

[0065] The positive electrode layer in the present disclosure is a layer containing at least a positive electrode active material. In addition, the positive electrode layer may further contain at least one of a solid electrolyte, a conductive material, and a binder as required.

[0066] The positive electrode active material is an active material that is usually defluorinated during discharge. Examples of the positive electrode active material include metal elements, alloys, metal oxides, and fluorides thereof. Examples of the metal elements contained in the positive electrode active material include Cu, Ag, Ni, Co, Pb, Ce, Mn, Au, Pt, Rh, V, Os, Ru, Fe, Cr, Bi, Nb, Sb, Ti, Sn, and Zn. Among them, the positive electrode active material is preferably Cu, CuF z ,Fe,FeF z 、Ag、AgF z . In addition, the above z is a real number greater than 0. In addition, as other examples of positive electrode active materials, carbon materials and their fluorides can be listed. As carbon materials, for example, graphite, coke and carbon nanotubes can be listed. In addition, as other examples of positive electrode active materials, polymer materials can be listed. As polymer materials, for example, polyaniline, polypyrrole, polyacetylene and polythiophene can be listed.

[0067] There is no particular limitation on the content of the positive electrode active material in the positive electrode layer. From the viewpoint of capacity, it is preferred that the content of the positive electrode active material is high. The content of the positive electrode active material is, for example, 30% by weight or more, 50% by weight or more, or 70% by weight or more. For the conductive material and the binder, since they are the same as those described in "A. Negative electrode material", the description here is omitted. In addition, for the solid electrolyte, it is the same as that described in "3. Solid electrolyte layer". In addition, there is no particular limitation on the thickness of the positive electrode layer, and it can be appropriately adjusted according to the composition of the battery.

[0068] 3. Solid electrolyte layer

[0069] The solid electrolyte layer in the present disclosure is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least a solid electrolyte. In addition, the solid electrolyte layer may further contain a binder as needed.

[0070] The solid electrolyte is not particularly limited as long as it is a material having fluoride ion conductivity, and is generally an inorganic fluoride. Examples of the inorganic fluoride include fluorides containing lanthanide elements such as La and Ce, fluorides containing alkaline earth elements such as Ca, Sr, and Ba, fluorides containing Group 14 elements such as Pb and Sn, and fluorides containing alkali elements such as Li, Na, K, Rb, and Cs.

[0071] In the present disclosure, the solid electrolyte in the solid electrolyte layer preferably contains the above-mentioned metal element (the same metal element as the metal element in the above-mentioned fluoride ion conductive material) and the element F. This is because the occurrence of a short circuit can be effectively suppressed.

[0072] In particular, it is preferred that the constituent elements of the solid electrolyte in the solid electrolyte layer be the same as the constituent elements of the fluoride ion conductive material in the negative electrode layer. 1- x Ba x F2 (0<x<1), the fluoride ion conductive material in the negative electrode layer is Ca 1-y Ba y In the case of F2 (0<y<1), it can be said that the types of constituent elements are the same. x and y may be the same or different. That is, the composition of the solid electrolyte in the solid electrolyte layer and the fluoride ion conductive material in the negative electrode layer may be the same or different.

[0073] In addition, in the present disclosure, the ionic conductivity of the solid electrolyte in the solid electrolyte layer may be greater than the ionic conductivity of the fluoride ion conductive material in the negative electrode layer. This is because overvoltage can be suppressed and a large specific capacity can be obtained. The ionic conductivity of the solid electrolyte in the solid electrolyte layer is set to C1, and the ionic conductivity of the fluoride ion conductive material in the negative electrode layer is set to C2. C1 may be the same as C2, or greater than C2. The value of C1 / C2 is, for example, greater than 1.00, greater than 1.05, or greater than 1.10.

[0074] The binder is the same as that described in "A. Negative electrode material", so description thereof is omitted here. The thickness of the solid electrolyte layer is not particularly limited and can be appropriately adjusted according to the configuration of the battery.

[0075] 4. Other components

[0076] The fluoride ion battery in the present disclosure preferably has: a positive electrode current collector for collecting current of the positive electrode layer, a negative electrode current collector for collecting current of the negative electrode layer, and a battery casing for accommodating the above-mentioned components. The shape of the current collector may be, for example, a foil, a mesh, a porous shape, etc. In addition, as the battery casing, a conventionally known battery casing may be used.

[0077] 5. Fluoride ion battery

[0078] The fluoride ion battery in the present disclosure may be a primary battery or a secondary battery, wherein a secondary battery is preferred. This is because it can be repeatedly charged and discharged, for example, it can be used as a vehicle-mounted battery. Furthermore, in the secondary battery, the use of a primary battery is also included (for the purpose of only discharging once after charging). In addition, as the shape of the fluoride ion battery, for example, a coin type, a laminate type, a cylindrical type, and a square type can be listed.

[0079] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative only, and any solution having substantially the same configuration and achieving the same function and effect as the technical concept described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.

[0080] Example

[0081] [Example 1]

[0082] (Synthesis of fluoride ion conductive materials)

[0083] As raw materials, CaF2 and BaF2 were prepared and weighed so as to be CaF2:BaF2=80:20 in terms of molar ratio. They were mixed and reacted by mechanical grinding using a planetary ball mill (manufactured by Fritsch Kaisha, PL-7), thereby obtaining a powdery fluoride ion conductive material (CaF2:BaF2).0.8 Ba 0.2 F2). Further, the conditions for mechanical grinding were set to 600 rpm, 20 hours, and a dry argon atmosphere.

[0084] (Preparation of negative electrode material)

[0085] Weigh powdered Mg (Mg metal), a fluoride ion conductive material (Ca 0.8 Ba 0.2 F2) and a conductive material (acetylene black) so that, expressed by weight ratio, it becomes powdered Mg: fluoride ion conductive material: conductive material = 35:62:3. By mechanical grinding using a planetary ball mill (manufactured by Fritsch Co., PL-7), they were mixed to prepare a powdered negative electrode material. The conditions for mechanical grinding were set to 600 rpm, 3 hours, and a dry argon atmosphere.

[0086] (Synthesis of solid electrolyte)

[0087] As raw materials, prepare CaF2 and BaF2, and weigh them so that, expressed by molar ratio, it becomes CaF2:BaF2 = 60:40. By mechanical grinding using a planetary ball mill (manufactured by Fritsch Co., PL-7), they were mixed and reacted to obtain a powdered solid electrolyte (Ca 0.6 Ba 0.4 F2). Further, the conditions for mechanical grinding were set to 600 rpm, 20 hours, and a dry argon atmosphere. Further, Ca 0.6 Ba 0.4 F2 has a higher ionic conductivity compared to the above-mentioned fluoride ion conductive material (Ca 0.8 Ba 0.2 F2) and the fluoride ion conductive materials (Ca 0.5 Ba 0.5 F2, Ca 0.4 Ba 0.6 F2, Ca 0.3 Ba 0.7 F2) in Examples 3 to 5 described later.

[0088] (Fabrication of evaluation cell (half cell))

[0089] An Al foil (counter electrode current collector), a compact (counter electrode) having 50 mg of PbF2 powder (containing 5 wt% acetylene black) formed on a Pb foil, 100 mg of a solid electrolyte (Ca 0.6 Ba 0.4F2) of pressed powder (solid electrolyte layer), 10mg of pressed powder of negative electrode material (working electrode), and Pt foil (working electrode collector) are stacked in sequence. Furthermore, the Pb foil in the counter electrode is arranged on the side in contact with the Al foil. The stack is arranged in a cylindrical container with an inner diameter of 11.28mm made of ceramic, and is clamped and fixed from both sides of the counter electrode collector and the working electrode collector with a stainless steel cylinder with a diameter of 11.28mm. In this way, an evaluation battery (half cell) was made.

[0090] [Example 2]

[0091] The ratio of CaF2 and BaF2 was changed so that the molar ratio became CaF2:BaF2=60:40, and the fluoride ion conductive material (Ca 0.6 Ba 0.4 F2), and a battery for evaluation was prepared in the same manner as in Example 1 except for the above.

[0092] [Example 3]

[0093] The ratio of CaF2 and BaF2 was changed so that the molar ratio was CaF2:BaF2=50:50, and a fluoride ion conductive material (Ca 0.5 Ba 0.5 F2), and a battery for evaluation was prepared in the same manner as in Example 1 except for the above.

[0094] [Example 4]

[0095] The ratio of CaF2 and BaF2 was changed so that the molar ratio became CaF2:BaF2=40:60, and the fluoride ion conductive material (Ca 0.4 Ba 0.6 F2), and a battery for evaluation was prepared in the same manner as in Example 1 except for the above.

[0096] [Example 5]

[0097] The ratio of CaF2 and BaF2 was changed so that the molar ratio became CaF2:BaF2=30:70, and the fluoride ion conductive material (Ca 0.3 Ba 0.7 F2), and a battery for evaluation was prepared in the same manner as in Example 1 except for the above.

[0098] [Comparative Example 1]

[0099] Weigh powdered In (In element), fluoride ion conductive material (Ca 0.8 Ba 0.2F2), and a conductive material (acetylene black) were mixed so that the weight ratio of In:fluoride ion conductive material:conductive material was 30:65:5. A negative electrode material and an evaluation battery were prepared in the same manner as in Example 1 except that the obtained mixture was used.

[0100] [evaluate]

[0101] (XRD measurement)

[0102] X-ray diffraction measurements were performed on the negative electrode materials obtained in Examples 1 to 5. Specifically, the measurements were performed using a SmartLab manufactured by Rigaku Corporation and a concentration method using CuKα radiation. The results are shown in Figure 2 middle.

[0103] like Figure 2 As shown in , the peak derived from Mg, the peak derived from the Ca-rich fluoride ion conductive material, and the peak derived from the Ba-rich fluoride ion conductive material were confirmed in Examples 1 to 5. In addition, in Example 1, the peak of CaF2 was also confirmed as an unreacted raw material (residue component).

[0104] (Composition Analysis)

[0105] The composition analysis was performed on the negative electrode materials obtained in Examples 1 to 5. Specifically, the surface of the pellet obtained by pressing the obtained negative electrode material was analyzed by mapping measurement with the observation field magnification of 1000 times using SEM-EDS (SU-8220, Hitachi High-Technologies Corporation; EMAX Evolution, Oxflow Instruments Corporation). The results are shown in Table 1.

[0106]

Table 1

[0107]

[0108] As shown in Table 1, the atomic ratio of Ba to Ca matched the value in the feed (raw material) and the measured value, and it was confirmed that the desired negative electrode material was synthesized.

[0109] (Discharge and charge test)

[0110] The evaluation cells (half cells) prepared in Examples 1 to 5 and Comparative Example 1 were subjected to discharge and charge tests to determine the reversible capacity and average operating potential. Specifically, the half cells were placed in a sealed container and the container was evacuated while the test was performed at 200°C. First, the cells were charged at a current density of 50 μA / cm 2Discharge (operate towards low potential). Next, charge with the same current density (operate towards high potential). The cut-off potential is set to -2.65V (vs. Pb) during discharge. 2+ / Pb), set to -1.00V (vs.Pb) during charging 2+ However, as a condition for terminating the charge, a capacity limit is set so that the test ends when the charge capacity does not exceed the discharge capacity.

[0111] The charge and discharge curves of Examples 1 to 5 and Comparative Example 1 are shown in Figure 3 In. In addition, Figure 3 The horizontal axis (specific capacity) of each graph in the figure is expressed by the Ca content in the negative electrode material. 1-x Ba x The weight of F2 (fluoride ion conductive material) is normalized. In addition, the results of the reversible capacity of Examples 1 to 5 are shown in Figure 4 The results of the reversible capacity and the average working potential are shown in Table 2. The average working potential was calculated by taking the average of the potentials when 50% of the capacity was taken out during discharge and charge.

[0112]

Table 2

[0113]

[0114] like Figure 3 As shown in , in Examples 1 to 5 and Comparative Example 1, discharge and charge can be performed without short circuit. In addition, the results of the cyclic voltammetry test (reaction potential investigation of the material) conducted by the inventors and others confirmed that for the negative electrode material (original Ca 1-x Ba x F2(プリスティンCa 1-x Ba x F2)) is -2.65V (vs.Pb 2+ / Pb) defluorination occurs at a low potential. 1-x Ba x In the evaluation cell (half cell) in which F2 was used as the negative electrode material, a short circuit occurred as defluorination proceeded.

[0115] On the other hand, in Examples 1 to 5 and Comparative Example 1, it is considered that the addition of metal materials (Mg, In) increases the Ca 1- x Ba x The defluorination potential of F2 shifts to a higher direction, so that no defluorination from the solid electrolyte layer (original Ca 0.6 Ba 0.4 F2) can inhibit the occurrence of short circuits.

[0116] In addition, as shown in Table 2, the average working potential of the negative electrode materials in Examples 1 to 5 was approximately -2.3 V (vs. Pb 2+ / Pb), the average working potential of the negative electrode material in Comparative Example 1 became -2.16 V (vs. Pb 2+ / Pb). That is, it was confirmed that the negative electrode materials in Examples 1 to 5 operate at a lower potential than the negative electrode material in Comparative Example 1. Here, as a representative positive electrode active material for a fluoride ion battery, it is assumed that a negative electrode material with an operating potential of about +0.7 V (vs. Pb 2+ / Pb) of Cu. Assuming that Cu is used as the positive electrode active material in a fluoride ion battery (full battery), the operating voltage (positive electrode operating potential - negative electrode operating potential) is 3.05V in Example 1, 3.04V in Example 2, 3.06V in Example 3, 3.05V in Example 4, and 3.02V in Example 5. The operating voltage of Comparative Example 1 is 2.86V. In this way, it is confirmed that when Mg material is used, the occurrence of short circuit can be suppressed in the same way as when In material is used, and further, the decrease in operating voltage can be suppressed compared to the case of using In material.

[0117] In addition, if Figure 4 As shown in Table 2, it was confirmed that Example 3 (x = 0.5) and Example 4 (x = 0.6) showed a significantly large reversible capacity. 1-x Ba x The value of x in F2 gives a negative electrode with excellent reversible capacity. This is believed to be because Figure 3 In the charge and discharge curves shown in , in Examples 3 and 4, compared with other Examples, there are regions where the gradient of the discharge curve is gentle at the initial, middle, and final stages of discharge, so the overvoltage is suppressed under the compositions of Examples 3 and 4. The reason for this is not clear, but it is speculated that the ion transport characteristics in the negative electrode depend on the value of x, and its characteristics are maximized under the composition of the above Examples.

[0118] [Example 6]

[0119] (Synthesis of fluoride ion conductive materials)

[0120] As raw materials, LaF3 and BaF2 were prepared and weighed so that the molar ratio was LaF3:BaF2=90:10. They were mixed by mechanical grinding using a ball mill and then calcined in an argon atmosphere to react. Thus, a powdery fluoride ion conductive material (LaF3:BaF2) was obtained. 0.9 Ba 0.1 F 2.9). The mechanical polishing conditions were set to 600 rpm, 20 hours, and dry argon atmosphere, and the calcination conditions were set to 800° C., and 3 hours.

[0121] (Preparation of negative electrode materials)

[0122] Weigh the powdered Mg (Mg element), fluoride ion conductive material (La 0.9 Ba 0.1 F 2.9 ) and a conductive material (acetylene black) were mixed so that the weight ratio of powdered Mg:fluoride ion conductive material:conductive material was 27:70:3. A negative electrode material was prepared in the same manner as in Example 1 except that the obtained mixture was used.

[0123] (Production of Evaluation Cell (Half Cell))

[0124] As the solid electrolyte layer, 150 mg of La was used. 0.9 Ba 0.1 F 2.9 An evaluation battery was prepared in the same manner as in Example 1, except that 15 mg of the powder compact of the negative electrode material was used as the working electrode.

[0125] [Comparative Example 2]

[0126] Weigh powdered In (In element), fluoride ion conductive material (La 0.9 Ba 0.1 F 2.9 ) and a conductive material (acetylene black) were mixed so that the weight ratio was 20:80:0 for powdered In:fluoride ion conductive material:conductive material. A negative electrode material and an evaluation battery were prepared in the same manner as in Example 6 except that the obtained mixture was used.

[0127] (Discharge and charge test)

[0128] The evaluation cells (half cells) prepared in Example 6 and Comparative Example 2 were subjected to discharge and charge tests to determine the reversible capacity and average operating potential. Specifically, the half cells were placed in a sealed container and the container was evacuated while the test was performed at 140°C. First, the current density was 10 μA / cm 2 The battery is discharged (operated in the direction of low potential). Next, it is charged at the same current density (operated in the direction of high potential). The cut-off potential is set to -2.40 V (vs. Pb) during discharge. 2 + / Pb), set to -1.00V (vs.Pb) during charging 2+ / Pb). However, as a condition for ending the charge, a capacity limit is set, and the test is set to end in a manner such that the charge capacity does not exceed the discharge capacity.

[0129] The charge and discharge curves of Example 6 and Comparative Example 2 are shown in Figure 5 In. In addition, Figure 5 The horizontal axis (specific capacity) of each figure is La in the negative electrode material. 0.9 Ba 0.1 F 2.9 The weight of the fluoride ion conductive material was normalized. Table 3 shows the results of the reversible capacity and average working potential of Example 6 and Comparative Example 2.

[0130]

Table 3

[0131]

[0132] like Figure 5 As shown in , in both Example 6 and Comparative Example 2, discharge and charge can be performed without short circuit. In addition, the results of the cyclic voltammetry test (reaction potential investigation of the material) conducted by the inventors confirmed that for the negative electrode material (original La 0.9 Ba 0.1 F 2.9 ) is -2.40V(vs.Pb 2+ / Pb) defluorination occurs at a low potential. 0.9 Ba 0.1 F 2.9 In the evaluation cell (half-cell) used as a negative electrode material, a short circuit occurred as defluorination proceeded.

[0133] On the other hand, it is considered that in Example 6 and Comparative Example 2, the addition of metal materials (Mg, In) increases the concentration of La. 0.9 Ba 0.1 F 2.9 The defluorination potential shifts to a higher direction, so that no defluorination from the solid electrolyte layer (the original La 0.9 Ba 0.1 F 2.9 ) can inhibit the occurrence of short circuits.

[0134] In addition, as shown in Table 3, the average working potential of the negative electrode material in Example 6 was -2.20 V (vs. Pb 2+ / Pb), the average working potential of the negative electrode material in Comparative Example 2 became -1.79 V (vs. Pb 2+= / Pb). That is, it was confirmed that the negative electrode material in Example 6 operates at a lower potential than the negative electrode material in Comparative Example 2. Here, as a representative positive electrode active material of a fluoride ion battery, it is assumed that a negative electrode material with an operating potential of about +0.7 V (vs. Pb 2+ / Pb) of Cu. Assuming that Cu is used as the positive electrode active material in a fluoride ion battery (full battery), the operating voltage (positive electrode operating potential - negative electrode operating potential) is 2.90V in Example 6. The operating voltage of Comparative Example 2 is 2.49V. In this way, it is confirmed that when using Mg material, the occurrence of short circuit can be suppressed in the same way as when using In material, and further, the decrease in operating voltage can be suppressed compared to the case of using In material.

Claims

1. A fluoride ion battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein: The negative electrode layer contains a negative electrode material, and the negative electrode material contains: Mg element; and Fluoride ion conductive material, wherein the fluoride ion conductive material is Ca 1-x Ba x F2, where x satisfies 0.45≤x≤0.65, The ratio of the Mg element in the negative electrode material is 30 wt % or more and 50 wt % or less, The ratio of the fluoride ion conductive material in the negative electrode material is 60 wt % or more and 80 wt % or less, The fluoride ion conductive material functions as a negative electrode active material during charge and discharge. The fluoride ion conductive material is in the form of particles, with an average particle size D 50 is 0.1 μm or more and 50 μm or less, The ion conductivity of the solid electrolyte in the solid electrolyte layer is equal to or higher than the ion conductivity of the fluoride ion conductive material in the negative electrode layer.

2. The fluoride ion battery according to claim 1, wherein: The solid electrolyte in the solid electrolyte layer is Ca 1-x Ba x F2, where 0 <x<1。

Citation Information

Patent Citations

  • Fluoride ion battery and method for manufacturing the same

    JP2018077987A

  • Composite electrode materials for fluoride-ion electrochemical cells

    CN110582874A